Gliricidia intercropping supports soil organic matter stabilization at Makoka Research Station, Malawi - Maier, Rebekka; Schack-Kirchner, Helmer; Nyoka, Betserai Isaac; Lang, Friederike (Geoderma Regional, 2023)
Intercropping agriculture with legume trees is a promising strategy to improve soils with low soil organic matter (SOM) and nitrogen (N) contents, which is a common problem in many Southern African regions. Objective of this research was to explore long-term effects of legume-intercropping on SOM pools and soil fertility. We examined a maize-based cropping system with gliricidia (Gliricidia sepium) as intercropping legume tree on a Ferric Lixisol in Southern Malawi. The experimental trial at Makoka Research Station was in its 29th year of management with leaf biomass incorporated into the soil regularly. We determined concentrations of organic carbon (C) and N, exchangeable cations, and available phosphorus (P) of topsoil samples (0–20 cm). We used density fractionation of SOM to gain fractions that roughly approximate SOM pools with fast turnover (not associated to soil minerals), intermediate turnover (occluded within soil aggregates) and slow turnover (mineral associated SOM). We further determined water dispersible clay (WDC) and pedogenic oxides, as these are often involved in the C-stabilization process in tropical soils. Maize-gliricidia intercropping plots showed higher soil pH-values, and higher concentrations of exchangeable Mg and Ca than plots with maize monoculture. In addition, significantly higher contents of C (17.3 vs. 7.03 g kg−1) and N (1.51 vs. 0.7 g kg−1) were found at intercropping plots indicating a C-sequestration rate of 0.3 g C kg−1 a−1, while monoculture induced the loss of SOM with a rate of −0.1 g C kg−1 a−1. C and N contents doubled in pools with fast and with slow turnover and increased by >300% in SOM pool where C and N is bound in soil aggregates. Concomitantly, WDC was significantly lower in intercropping plots than in monoculture plots. Our data emphasize the fast turnover of SOM in subtropical soils and indicate that SOM in arable soils decreases continuously without suitable C-input strategy. Maize-gliricidia intercropping had positive effects on biomass production and C-input at Makoka Research Station and improved soil fertility. In addition, aggregate formation was enhanced and storage of SOM within aggregates and at mineral surfaces increased. Our results indicate a great potential of maize-gliricidia intercropping for improved C management in subtropical Lixisols. Intensive monitoring seems to be promising to validate and quantify the impacts of this measure.